The occurrence of Natsushima bifurcata (Polychaeta : Nautiliniellidae) in Acharax hosts from mud volcanoes in the Gulf of Cadiz (south Iberian and north Moroccan Margins) - Ravara, Ascensão (2007)
Fifteen specimens of nautiliniellid polychaetes were found in the mantle cavity of bivalves of the genus Acharax (Solemyidae) collected in several mud volcanoes from the Gulf of Cadiz. They were identified as Natsushima bifurcata Miura and Laubier (1990), a species previously known only from Sagami Bay (Japan). The morphological comparison of these specimens with the holotype suggests that they belong to the same morphological species, although further studies should consider whether they could be genetically different. The ecology of the species is discussed in relation to the available information on the family. The occurrence of Natsushima bifurcata in the Gulf of Cadiz is the first record of the species in the North Atlantic.